ANALISIS DATA ANGIN PERMUKAAN DI BANDARA SYARIF KASIM II PEKANBARU MENGGUNAKAN METODE WINDROSE - Saragih, Rino Wijatmiko; Siregar, Putri Santy (Jurnal Widya Climago, 2021)
Research on surface wind patterns has been carried out in an effort to minimize aircraft accidents at Sultan Syarif Kasim II Airport Pekanbaru, Riau. Wind direction and speed data were obtained from synoptic observations of the Syarif Kasim II Pekanbaru Meteorological Station from January to December during 1991 - 2020 (for the last 29 years). The data is then processed using the WRPLOT (Wind Rose Plots for Meteorological Data) application which can show the direction and difference in the magnitude of the wind speed and produce an image of the wind pattern in the form of a wind rose diagram. From the results of this writing, it is known that the dominant wind blows from the south (157 - 202°) with a percentage of 27.18%, then followed by the dominant wind blowing from the Northwest (292 - 337°) with a percentage of 14.68% and then the dominant wind direction from the Southeast (112 - 157°) with a percentage of 9.60%. The dominant wind speed is 6 – 9 knots with a percentage of 48.01%, then dominant with a speed of 3 – 6 knots with a percentage of 34.15%, and calms wind speed with a percentage of 7.23%. The conclusion of this paper is that the condition of the wind direction and speed at Sultan Syarif Kasim II Airport Pekanbaru is still a safe category for the takeoff and landing process.